PEMBUATAN OATMEAL COOKIES DENGAN SUBSTITUSI TEPUNG UBI JALAR KUNING - Ira Handayani; Ayu Zakiyah (Garina, 2021)
Cookies are a type of patisserie product that is in great demand by the public. Most types of cookies need wheat flour as the basic ingredient, so that causing increased imports of wheat flour. To get around the amount of use of wheat flour so can be used flour from local food ingredients such as yellow sweet potato flour. Purpose of the research: 1) Knowing the composition of the ingredients that used in the making of oatmeal cookies with yellow sweet potato flour substitution; 2) Knowing the process of making oatmeal cookies with yellow sweet potato flour substitution; 3) Knowing the level of people's preference towards oatmeal cookies with yellow sweet potato flour substitution. The methods used in this research are the method of literature, experimentation, documentation, questionnaire, sensory testing, hedonic testing and data analysis. Yellow sweet potato flour used was 15%, 30%, 45% of the weight of the flour. The results showed that oatmeal cookies with yellow sweet potato flour were the most preferred and accepted by the panelists as products with the substitution of yellow sweet potato flour as much as 30%.